Imperfect Sympathies - Page, J. author. aut Link
XIV, 257 p.
Keywords: Judith W. Page argues that the 'cultural revolution' of sympathy and sentiment in British literature from 1770-1830 influenced the representations of Jews and Judaism. Page draws on historical materials and primary documents by and about Jews of the period, as well as a variety of authors and literary genres. She argues that there is a tension between the Romantic impulse to admire and sympathize with Jews and Judaism on the one hand, and the traditions of anti-semitism and conversionist philo-Semitism on the other. This often unresolved tension in the literature reflects the political and cultural struggles of the time, as well as the dilemma of Romanticism, which advocates sympathy but doesn't always accommodate difference.